Assessing anger regulation in middle childhood: development and validation of a behavioral observation measure - Rohlf, Helena L.; Krahé, Barbara (Frontiers in Psychology, 2015)
An observational measure of anger regulation in middle childhood was developed that facilitated the in situ assessment of five maladaptive regulation strategies in response to an anger-eliciting task. 599 children aged 6-10 years (M = 8.12, SD = 0.92) participated in the study. Construct validity of the measure was examined through correlations with parent- and self-reports of anger regulation and anger reactivity. Criterion validity was established through links with teacher-rated aggression and social rejection measured by parent-, teacher-, and self-reports. The observational measure correlated significantly with parent- and self-reports of anger reactivity, whereas it was unrelated to parent- and self-reports of anger regulation. It also made a unique contribution to predicting aggression and social rejection.